PENEGAKAN HUKUM PERETASAN SITUS WEBSITE OLEH SINDIKAT JUDI ONLINE - Mansur, Habil Ma’ruf; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: In this paper, the author will examine legal issues regarding law enforcement against website hacking In this paper, the author will examine legal issues regarding law enforcement against website hacking committed by online gambling syndicates, where lately crimes related to website hacking are increasingly widespread, this is clearly seen from the many cases that continue to occur, hacking itself is included in cybercrime, In some cases that occur regarding hacking cases, it has not explained in detail about how the regulation, enforcement, legal consequences, obstacles, shortcomings and so on, so the author feels the need to discuss it all to then clarify how the enforcement of hacking crimes committed by online gambling syndicates. Here, the author uses a normative research method, which is a research method that uses norms or laws and regulations as its source. This kind of research is also known or called the library research method because it uses secondary data, namely laws, journals, books and so on and uses a normative juridical approach. Keywords: hacking, online gambling syndicates, law enforcement, website